Sostenibilidad del ciclo de vida en el cultivo de maíz (zea mays) en la zona norte de la provincia de Los Ríos - Torres Morales, Jacqueline Lisbeth (2021)
The present project entitled "Sustainability of the life cycle in the cultivation of corn (Zea mays) in the north of the province of Los Ríos", considered small farmers from the cantons of Quevedo, Ventanas, Puebloviejo, Mocache and Quinsaloma. The inadequate agricultural practice, due to the high application of agrochemicals for the fumigation and unjustified burning of stubble, affects the quality of natural resources and the quality of life of living organisms. Therefore, evaluating the sustainability of the life cycle of corn in the province of Los Ríos, consisted of analyzing the conventional agricultural practices for the production of corn in the study area to 260 small farmers. A survey was applied to determine the degree of knowledge about the Sustainable Agriculture Standards; the identification of significant differences by Chi square analysis. The significance level of 0.05 (5%) shows that there is no significant difference in the acceptance of Sustainable Agriculture Standards since the level of technical preparation of the farmers and the conditions of the farms are not suitable for implementation. of strategies. However, implementing a continuous training plan on the methodology would increase the chances of using agricultural residues such as livestock feed and compost. After the training on the LISA methodology, it was determined that the no-tillage technique with permanent bed presented a resistance greater than 50% and the Push-Pull system of biological control with 94.8% in the five cantons. A difference was evidenced with the Integrated Agriculture method with crop rotation and no tillage with an average acceptance of 65.2% in the study area. The training of new techniques with a monitoring system is necessary, which achieves the implementation of sustainable agriculture in this area of economic importance, to contribute to the fulfillment of the goals of Sustainable Development Goal 3, 6 and 13. Keywords: Integrated agriculture, Reduced tillage, LISA method, Agricultural practices.